DETERMINANTS OF VITAMIN D STATUS ON PRESCHOOL CHILDREN AGED 48-59 MONTHS OLD IN KENDARI - Sri Anna Marliyati; Faisal Anwar; Ikeu Ekayanti; Nurnashriana Jufri (Universitas Airlangga, 2023)
Vitamin D deficiency is a world health problem because it affects more than one billion children and adults. This study aims to identify factors associated with vitamin D status in preschool children aged 48-59 months old. The study used a cross-sectional design on 96 preschool children aged 48-59 months old in Kendari city. The withdrawal of research subjects used a consecutive sampling method. Data on the characteristics of the respondents and the characteristics of the parents of the respondents were obtained through interviews using a questionnaire. A digital scale and a stadiometer determine nutritional status by measuring body weight and height. The Chemiluminescent Microparticle Immunoassay (CMIA) method was used to determine serum levels of 25(OH)D. Meanwhile, the data analysis used the Chi-Square test, Kolmogorov Smirnov, and independent sample T-test. The prevalence of preschool children aged 48-59 months with vitamin D deficiency was 9.4%, 57.3% insufficiency, and 33.3% sufficiency. There was no relationship between gender, BMI/U, physical activity, vitamin DÂ admissions, length of sun presentation, parental income, and mother's education with vitamin D status of preschool children aged 48-59 months old in Kendari city (P > 0.05). In this case, a strategy is needed to increase vitamin D intake through mandatory vitamin D fortification in the food industry and evaluating the time and amount of light exposure to sunlight is required to prevent vitamin D deficiency in preschoolers.